Evaluation of Mental Health Status of Nursing Students of the Islamic Azad University, Sari, Iran, during the Covid-19 Pandemic in Winter 2021 - mohammad taha saadati rad; Faezeh Mashhadi; Homeyra Akbarzadeh; Fatemeh Mohseni; Sara Aghaei; Fatemeh haddad samani; Malihe Ram; Mehrangiz Ghabimi (Mazandaran University of Medical Sciences, 2021)
Introduction and purpose: One of the important missions of nursing education is the mental health of nursing students who play an important role in promoting the health of the community. It is necessary to maintain nursing studentschr('39') mental health due to their prominent role in providing health services during the coronavirus disease 2019 (COVID-19) pandemic. Therefore, this study was conducted to determine the mental health status of nursing students in the School of Nursing, Islamic Azad University, Sari Branch, Sari Iran, during the COVID-19 pandemic. Methods: This analytical study was conducted based on a descriptive cross-sectional method using the census method on all nursing students of Islamic Azad University, Sari Branch. Data collection tools were a demographic form and the 12-item General Health Questionnaire.   Results: Totally, 278 participants completed the study, among which 70 (25.2%) participants worked in the COVID-19 hospitals and 208 (74.8%) participants did not work. The highest and lowest mean scores of mental health were related to the first-year and sixth-semester students (5±3.10 and 3.7±2.51), respectively. Moreover, the mean of mental health was significantly higher in participants who had contact with COVID-19 patients than others, indicating poor mental health among them  (P<0.05). Conclusion: According to the findings, it is necessary to pay attention to the mental health of nursing students during the corona pandemic; in this respect, it is suggested to have an effective role in the improvement of mental health of nursing students by holding mental health workshops, changing the conditions of educational environments during the COVID-19 pandemic, and providing counseling.